Public health in 1948 : Remarkable statistics. The first months of the National Health Service
1950-03-31 1950 1950s 8 pages A substantial and very welcome reduction in deaths from enteritis and diarrhoea in children under two years occurred during the year, and outbreaks of epidemic diarrhoea of unknown origin in infants, which had been a distressing feature since 1945, were less often reported. [Pp. 51 and 94] Sir Wilson Jameson reminds mothers that in breast feeding they themselves have an excellent defence for their children against infant diarrhoea, which they alone can provide, and that it is the salvation of many babies. [P.8] Food Poisoning. Outbreaks were more numerous (or perhaps more investigated) than ever, those investigated having risen from 412 in 1945 to 964 in 1948. Of the 962 outbreaks that appeared to be of bacterial origin 908 were caused by a member of the Salmonella group. Four-fifths of these salmonella outbreaks, however, affected single patients only. Food poisoning is largely preventable and could be abolished if everyone realised the precautions necessary when dealing with food. First class equipment and the best methods of manufacture will fail if a person handling food is suffering from some septic condition of the hands, nose or throat, or has forgotten to wash before beginning work or after visiting the closet. Education is required of employers and employees in the trade, of school children and of the general public. Many local authorities are encouraging suppliers to supply and consumers to demand clean foods. [Pp. 8 and 54] VENEREAL DISEASES The steep fall in the clinic figures for early syphilis in 1947 continued in 1948, but was less marked in some large seaports and there still seem to be considerable reservoirs of infection in a few great inland cities. Gonorrhoea has also declined. Penicillin continues to fulfil its early promise as an effective therapeutic agent in both diseases and their treatment has been both simplified and shortened by its use. Pp. 63 and 234] CANCER Deaths from cancer in 1948 numbered 79,537, an increase of 1,687 upon those in 1947. Male deaths numbered 40,130, an increase of 1,187, and female 39,407, an increase of 500. These increases are largely accounted for by the greater number of persons living at the ages most subject to cancer, but there was a slight increase in the comparative mortality index for males. For females the index declined slightly. Two thirds of the male increase was due to cancer of the respiratory system. [Pp. 3, 9, 67 and 229] The policy of centralisation, on the principle that cancer can only be effectively treated in a small number of fully equipped hospitals with which are associated all necessary laboratory and research facilities, is held to have put this country ahead of many other countries in the general management of cancer. [P. 68] TUBERCULOSIS The over-all mortality from all forms of the disease reached a new low record in 1948 (505 per million living). A notable exception to this general improvement is found among males over the age of 55; the mortality experienced by females at this age was only from one fourth to one fifth of that of the males. The proportion of deaths from tuberculosis occurring in persons not notified before death remains high and is increasing. [P. 107] The continuing shortage of institutional accommodation impeded the segregation of infective patients from their home contacts, and, although measures were being taken to bring modern treatment into the homes of patients, it was difficult there to enforce the necessary isolation, and so many of the - 4 - 292/847/5/38